The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1177/20427530211022922
|View full text |Cite
|
Sign up to set email alerts
|

Learning whiplash: Chinese College EFL learners’ perceptions of sudden online learning

Abstract: As coronavirus disease 2019 swept through mainland China, students were forced to quickly switch to learning online. This study aimed to capture college Chinese English as a Second/Foreign Language (ESL/EFL) learners’ perceptions of rapidly switching to online learning at two colleges in China’s southern Guangdong Province. A bilingual (Chinese/English) online survey was used to collect data. The participants ( n = 504) responded to a survey about their feelings and perceptions of sudden online learning, a ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Derakhshan et al (2021) reported boredom as one of the main issues among EFL Iranian students in online classes, which was particularly due to a lack of peer interaction, teacher-student interaction, and interpersonal relationships. Barnhart, Li and Thompson (2022) also reported that 79% of students admitted to getting drowsy and/or falling asleep during their online classes. Hence, peer interaction seems to be necessary for EFL classes, a limitation that needs to be addressed in online EFL classes.…”
Section: Lack Of Peers' Physical Presencementioning
confidence: 99%
See 2 more Smart Citations
“…Derakhshan et al (2021) reported boredom as one of the main issues among EFL Iranian students in online classes, which was particularly due to a lack of peer interaction, teacher-student interaction, and interpersonal relationships. Barnhart, Li and Thompson (2022) also reported that 79% of students admitted to getting drowsy and/or falling asleep during their online classes. Hence, peer interaction seems to be necessary for EFL classes, a limitation that needs to be addressed in online EFL classes.…”
Section: Lack Of Peers' Physical Presencementioning
confidence: 99%
“…Basic Users avoided class participation due to the embarrassment of not being able to follow the instructions, while Independent and Proficient Users merely avoided unnecessary class tasks to focus more on what they found to be more useful to them. Thirdly, the only challenge which was similarly perceived by and influential on all the participants was the lack of peers' physical presence, which led to feelings of loneliness and boredom (Cancino & Avila, 2021;Derakhshan et al, 2021;Barnhart, Li, & Thompson, 2022).…”
Section: Lack Of Nonverbal Communication Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid learning is a challenge for many parties, as research (Babin et al, 2022) states that students enrolled in hybrid learning have less than optimal performance in online learning sessions. Meanwhile, (Barnhart et al, 2022) stated that students prefer hybrid learning patterns over fully online learning. Students must develop self-regulated learning (SRL) to monitor their learning progress independently Hanna, 2021).…”
Section: Introductionmentioning
confidence: 99%